2020
DOI: 10.1101/2020.12.10.418772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOE4 affects basal and NMDAR mediated protein synthesis in neurons by perturbing calcium homeostasis

Abstract: Apolipoprotein E (APOE), one of the primary lipoproteins in the brain has three isoforms in humans – APOE2, APOE3, and APOE4. APOE4 is the most well-established risk factor increasing the pre-disposition for Alzheimer’s disease. The presence of the APOE4 allele alone is shown to cause synaptic defects in neurons and recent studies have identified multiple pathways directly influenced by APOE4. However, the mechanisms underlying APOE4 induced synaptic dysfunction remain elusive. Here, we report that the acute e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Our results, in concert with previous data, suggest that calcium signaling disruptions may play an important role in APOE4 effects and start early in the brain. Prior studies have found that APOE4 triggers greater intracellular calcium levels than APOE3, and impacts NMDA-receptor-mediated signaling in cultured neurons to disrupt calcium signaling and protein translation 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results, in concert with previous data, suggest that calcium signaling disruptions may play an important role in APOE4 effects and start early in the brain. Prior studies have found that APOE4 triggers greater intracellular calcium levels than APOE3, and impacts NMDA-receptor-mediated signaling in cultured neurons to disrupt calcium signaling and protein translation 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the dysregulation of calcium homeostasis by APOE ε4 leads to its impaired protein synthesis response (Figure 2A). 48 …”
Section: The Role Of Apoe In Ad Pathophysiologymentioning
confidence: 99%
“…The UPR can reduce ER protein folding load by inhibiting global protein translation, but chronic activation can stimulate pro‐inflammatory signalling converging on NF‐ĸB and apoptosis (Dose et al, 2016). Interestingly, UPR activation has been linked to ApoE4 expression in E4‐TR mouse brain (Zalocusky et al, 2021; N. Zhao et al, 2020) and ApoE4 fragment accumulation in vitro (Zhong et al, 2009), while in parallel ApoE4 may suppress global translation via prolonged neuronal calcium influx (Ramakrishna et al, 2021). Speculatively, ApoE4 may converge on ER stress and mitochondrial dysfunction via direct ApoE4 fragment accumulation and indirectly via chronically elevated intracellular calcium levels (Hit 7).…”
Section: Hit 6: Lipid and Cellular Metabolism Disruptionmentioning
confidence: 99%
“…Early observations demonstrated that the direct application of full length or truncated ApoE to neuronal cells resulted in an increase in intracellular calcium (Ohkubo et al, 2001; Qiu et al, 2004; Tolar et al, 1999; Wang & Gruenstein, 1997) and calcium bursting responses (Konings et al, 2021). Further, ApoE4 specifically elevated intracellular calcium levels relative to ApoE3 and was shown to be likely mediated by ApoE receptor activation of L‐type voltage gated calcium channels (VGCCs) and NMDARs, which may involve prolonged calcium influx dynamics (Ohkubo et al, 2001; Qiu et al, 2003; Ramakrishna et al, 2021; Veinbergs et al, 2002; Figure 7, Path A). Further, NMDAR‐dependent accumulation of intracellular calcium and induced cell death was also shown to be exacerbated by injury in the presence of APOE4 or APOE ‐KO but was rescued by APOE3 in vitro (Jiang et al, 2015).…”
Section: Hit 7: Calcium Dyshomeostasismentioning
confidence: 99%
See 1 more Smart Citation